Kejadian ISPA dan Status Gizi Balita pada Keluarga Perokok di Desa Andabia Kecamatan Anggaberi Kabupaten Konawe - Fitri, Nesya Desrianti; Ananda, Siti Hadrayanti; Ihsan M, Habib; Dhesa, Desiderius Bela; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2023)
Acute Respiratory Infection is an infectious disease of the upper and lower respiratory tract caused by bacteria or viruses enters the respiratory system, causing symptoms like a cough, runny nose, hoarseness, and fever. and mucus discharge for less than 14 days. The problem of nutrition is essentially a public health problem whose handling cannot be done by approaching medical services and health services alone. The causes of nutritional problems are multifactorial, so they must involve various related sectors. Despite the fact that smoking can reduce morbidity and mortality, it remains a public health issue. In addition to leading to mortality and morbidity. This type of research is descriptive research. Descriptive research is research with a method to describe a research result. The Simple Random Sampling method was used to collect the sample for this study. Univariate data were obtained in the form of sex, weight/age, and number of smokers.